Digital Communication Skills in Business: Their Impact on Millennials - Lingga, Ita Salsalina; Tjun , Lauw Tjun; Marpaung, Elyzabet Indrawati; Prayogo, Enny; Eddy , Endah Purnama Sari; Dwistia , Reynald Emmanuel; Widjaja, Kanisius Kevin (Universitas Mathla'ul Anwar Banten, 2024)
The world has made extraordinary developments in the field of internet technology since the industrial revolution 4.0 era, which was marked by a transformation towards digitalization in all aspects. We can see that digitalization has resulted in changes in communication patterns and information seeking, thus having a big impact on people's life patterns. Digital communication has greatly influenced face-to-face communication among the millennial generation. Technological developments not only have a positive impact on the millennial generation but also have negative impacts, such as: the communication process is changing from active to passive; reduced face-to-face communication; a lack of focus in communication; and online and virtual communication behavior. This is the background for conducting training to the millennials at GJKI Andir. Several points to be achieved through this community service activity are: (1) provide an understanding of what is meant by digital communication skills and their impact on the business world; (2) provide an understanding of the importance of digital communication skills for millennials and their negative impacts; and (3) provide an understanding of the main problems of digital communication and problem-solving solutions. The research results are targeted to be a reference regarding the importance of digital communication, problems, and solutions.